Pengaruh Kepadatan Medium MS0 terhadap Perkecambahan Biji Jagung (Zea mays L., Var.â€ Lokalâ€) secara In Vitro - Istiqhomah, Saniatul; Mukaromah, Arnia Sari; Rusmadi, Rusmadi (Al-Hayat: Journal of Biology and Applied Biology, 2019)
This study aims to determine the effect of MS0 medium density on maize in vitro seed germination. The sample used in this study is corn kernels from local variety (Zea mays L. var. ?Lokal?). This research was an experimental research with a quantitative method approach. The study used a Rancangan Acak Lengkap (RAL) with one treatment factor that is medium density MS0 with a degree of agar concentration are 4 gram, 6 gram, 8 gram and 10 gram each concentration repeated 3 times. Data analysis uses the One Way Analysis of Variant (ANOVA) test and if it shows significant results, test continued to BNJ test (Beda Nyata Jujur). The best growth results occur at low level medium density (agar 4 gram) based on parameters days of emerged buds, plant height, number of roots, number of leaves and wet weight of corn plantlets. Uji ANOVA showed that  F value calculated 41.333 bigger than F value table that is 4.07 with significance level 0,05. This result shows that H0 is rejected and Ha is accepted. The results are continued with the BNJ test. BNJ test obtained significantly different results on germination of corn kernels in all treatments. The wet weight of corn plantlets has a high influence on the organs (roots, stems and leaves) of plants. If the wet weight is high, the plant growth is significant and vice versa.